2021
DOI: 10.32604/ijmhp.2021.013072
|View full text |Cite
|
Sign up to set email alerts
|

Community Workers’ Social Support and Sleep Quality during the Coronavirus Disease 2019 (COVID-19): A Moderated Mediation Model

Abstract: To explore the relationship between social support and sleep quality of community workers in Wuhan during the coronavirus disease 2019 (the COVID-19 infection epidemic), this research constructed a mediating effect model to explore the mediating psychological mechanism of social support influencing sleep quality of front-line community workers. A total of 500 front-line community workers in Wuhan were investigated. We used the perceived social support scale (PSSS), the Connor-Davidson Resilience Scale (CD-RISC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Our findings on the significant associations of anxiety symptoms with female sex and poor financial status are consistent with elevated risk of anxiety symptoms in older women and socioeconomically disadvantageous older adults in earlier studies ( 55 57 ). Because family members are a significant source of social support for older Chinese adults and family support plays an important role in the mental well-being of older Chinese adults ( 58 60 ), our finding on the significantly higher risk of anxiety symptoms in older adults without a good family relationship is expected. In general, rural older adults are more likely to develop anxiety symptoms than urban older adults because of their lower socioeconomic status and the inadequate health service resources in rural regions ( 4 ).…”
Section: Discussionmentioning
confidence: 76%
“…Our findings on the significant associations of anxiety symptoms with female sex and poor financial status are consistent with elevated risk of anxiety symptoms in older women and socioeconomically disadvantageous older adults in earlier studies ( 55 57 ). Because family members are a significant source of social support for older Chinese adults and family support plays an important role in the mental well-being of older Chinese adults ( 58 60 ), our finding on the significantly higher risk of anxiety symptoms in older adults without a good family relationship is expected. In general, rural older adults are more likely to develop anxiety symptoms than urban older adults because of their lower socioeconomic status and the inadequate health service resources in rural regions ( 4 ).…”
Section: Discussionmentioning
confidence: 76%
“…Our results indicated that the stronger the organizational support was perceived by nurses, the higher was their psychological capital, which led to a reduction in insomnia. Many studies showed that better social support improved sleep quality by developing mental resilience (Lei et al, 2021) and reducing negative emotions (Grey et al, 2020). The role of positive psychology is extended in this study.…”
Section: Discussionmentioning
confidence: 73%
“…The COVID-19 pandemic has caused a dramatic loss of human life, posing unprecedented challenges to public health, food systems, and the workplace. More than 500 million laboratory-confirmed cases were documented as of 26 July 2022 [1]. Amid the highly contagious characteristic, unknown pathogenesis, and unclear modes of transmission of COVID-19 in 2020, prevention and control studies were hardly conducted.…”
Section: Introductionmentioning
confidence: 99%